1996
DOI: 10.1142/s0192415x96000050
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Activity of Scutellaria rivularis Extracts and Its Active Components, Baicalin, Baicalein and Wogonin

Abstract: Five extracts (n-hexane, chloroform, ethyl acetate, n-butanol and water) of Scutellaria rivularis Benth. were evaluated for their anti-inflammatory activity against carrageenan-induced paw edema in rats and compared with indomethacin. The result indicated that chloroform extract proved to be the most effective in all of the extracts. Consequently, three major components (baicalin, baicalein and wogonin) of the chloroform extract were further tested for their anti-inflammatory activity using the same model. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
2
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(165 citation statements)
references
References 0 publications
4
158
2
1
Order By: Relevance
“…Previous reports suggested that baicalin could inhibit tissue's inflammatory response through decreasing the release of TNF-α, IL-1 β, IL-6 and other factors which had been confirmed that might enhance osteoclast function and promote bone resorption directly or indirectly [11][12][13]. Wang GF [26] showed that the expression of RANKL mRNA stimulated by IL-1β was inhibited by baicalin after being treated for 12h and the inhibition reached its maximum at 48h.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous reports suggested that baicalin could inhibit tissue's inflammatory response through decreasing the release of TNF-α, IL-1 β, IL-6 and other factors which had been confirmed that might enhance osteoclast function and promote bone resorption directly or indirectly [11][12][13]. Wang GF [26] showed that the expression of RANKL mRNA stimulated by IL-1β was inhibited by baicalin after being treated for 12h and the inhibition reached its maximum at 48h.…”
Section: Discussionmentioning
confidence: 90%
“…It had been reported that baicalin exhibited antibacterial, anti-inflammatory and analgesic effects [5][6][7][8][9][10]. Many scholars found that baicalin could inhibit tissue's inflammatory response through decreasing the release of TNF-α, IL-1 β, IL-6 and other factors which had been confirmed that might enhance osteoclast function and promote bone resorption directly or indirectly [11][12][13].…”
Section: Introductionmentioning
confidence: 96%
“…Parts of the compounds have been reported to have the pharmacological activity related to H1 receptor inhibition by literatures. Lin found that Baicalein (ID 2102) and Baicalin (ID 2106) extracted from Scutellaria rivularis have the anti-inflammatory activity against carrageenan-induced paw edema in rats [22]. Cortisone (ID 6853) and cuscohygrine (ID 1836) were discovered to have the active of anti-allergy [23], [24].…”
Section: Top Scoring Compoundsmentioning
confidence: 99%
“…It is mainly distributed in southern China and has been used as an antitumor agent for lung cancer, digestive system cancer, hepatoma, breast cancer, and chorioepithelioma as well as an anti-inflammatory agent and a diuretic in China and Korea [1][2][3][4][5][6][7][8][9] . Extracts from S. barbata (ESB) have in vitro growth inhibitory effects on a number of human cancers including leukemia, colon cancer, hepatoma and skin cancer [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%